Resonance fluctuations of sandwich beam - Starovoytov Э. И.; Yarovaya А. В. (Chrezvychaynye situatsii: obrazovanie i nauka, 2006)
Considered fluctuations under resonance sandwich beam with filler under the action of local surface loads. For the kinematics description of carryings layers accepted the hypotheses Bernoulli. In hard compressed filler the precise ratio of a theory of elastic strength with linear approximating of movements of his its points from cross-sectional coordinate z are fair. Received the analytical deciding and conducted their numeric analysis. The capability of a development of a false resonance is investigated.